2003
DOI: 10.1038/oby.2003.100
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Complement Components in Omental Adipose Tissue in Obese Men

Abstract: Res. 2003;11:699-708. Objective: Accumulation of visceral fat is recognized as a predictor of obesity-related metabolic disturbances. Factors that are predominantly expressed in this depot could mediate the link between visceral obesity and associated diseases. Research Methods and Procedures: Paired subcutaneous and omental adipose tissue biopsies were obtained from 10 obese men. Gene expression was analyzed by DNA microarrays in triplicate and by real-time polymerase chain reaction. Serum C3 and C4 were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
171
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(188 citation statements)
references
References 45 publications
(54 reference statements)
9
171
1
3
Order By: Relevance
“…Cross-sectional studies have shown that obesity is associated with elevated plasma levels of C3 [4,[6][7][8][9][10], but the causal and temporal relations of this association have been unclear. The present study showed that C3 was strongly associated both with weight at baseline and weight at follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cross-sectional studies have shown that obesity is associated with elevated plasma levels of C3 [4,[6][7][8][9][10], but the causal and temporal relations of this association have been unclear. The present study showed that C3 was strongly associated both with weight at baseline and weight at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of these proteins increases in response to inflammation and infection, with a slower increase than the traditional acute-phase proteins [1][2][3]. Although hepatic production is the main source of these proteins, C3 and C4 are also expressed and secreted by other cells, for example, in adipose tissue [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C3 is the key protein of the complement cascade, and is abundantly present in plasma. In addition, C3 is found in the peritoneal fluid [8] as well as in subcutaneous and omental adipose tissue [9]. C3 is a contributor to the biomaterial-induced inflammation during blood contact [10], and recently C3 was demonstrated to be involved in the inflammatory host response against subcutaneous and intraperitoneally implanted…”
Section: Introductionmentioning
confidence: 99%
“…65 C3 and Factor B are positively correlated with body weight and visceral fat, and decrease after weight loss 66,67 ASP secretion by the adipose tissue is increased after meals and stimulates TG synthesis and decreases nonesterified FA release in adipocytes. 65 Levels of plasma ASP have been positively correlated with obesity, percent body fat and with insulin resistance.…”
Section: Inflammatory Proteins and Cytokinesmentioning
confidence: 99%